2004
DOI: 10.1038/sj.onc.1208360
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-type-1 matrix metalloproteinase confers tumorigenicity on nonmalignant epithelial cells

Abstract: Overexpression of membrane-type-1 matrix metalloproteinase (MT1-MMP) in tumor cells has previously been shown to enhance tumor growth and metastasis. To establish if MT1-MMP is also able to confer tumorigenicity on nonmalignant epithelial cells, we transfected human MT1-MMP cDNA into Madin-Darby canine kidney (MDCK) cells expressing a tetracycline-repressible transactivator. Induction of MT1-MMP in the absence of doxycycline (Dox) was associated with activation of exogenous MMP-2 as well as with formation of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 49 publications
9
36
0
Order By: Relevance
“…We also examined the effect of expressing MT1-MMP in SCC cells on the surrounding stroma using trichrome stain to label the collagen present in these tumors. Consistent with previously published reports demonstrating that MT1-MMP can induce fibrosis in vivo (62,63), SCC25-tet-MT and SCC25-tet-DC cells also induced a pronounced fibrotic reaction with increased collagen content as demonstrated by increased trichrome (blue) stain (Fig. 8C).…”
Section: Mt1-mmp Increases Cellular Aggregation and Myosin IIsupporting
confidence: 80%
“…We also examined the effect of expressing MT1-MMP in SCC cells on the surrounding stroma using trichrome stain to label the collagen present in these tumors. Consistent with previously published reports demonstrating that MT1-MMP can induce fibrosis in vivo (62,63), SCC25-tet-MT and SCC25-tet-DC cells also induced a pronounced fibrotic reaction with increased collagen content as demonstrated by increased trichrome (blue) stain (Fig. 8C).…”
Section: Mt1-mmp Increases Cellular Aggregation and Myosin IIsupporting
confidence: 80%
“…The expression of MT1-MMP in the centrosomes of either human or canine cells correlated with the presence of the proteolytic fragments of pericentrin. In addition, these events correlated with the induction of mitotic spindle aberrations and aneuploidy in non-malignant MDCK cells (18,23). The sequence alignment of the putative cleavage site in human and canine pericentrin (ALRRLLG 1156 2L 1157 FG and ALRRLLS 2068 2L 2069 FG, respectively) supported our biochemical and cellular experiments, because both Gly and Ser are compatible with the known cleavage preferences of MT1-MMP.…”
Section: Discussionsupporting
confidence: 62%
“…The presence of MT1-MMP in the pericentrosomal space correlated with the cleavage of human pericentrin-2 (kendrin), an integral and functionally important centrosomal, 3336-amino-acid residue long, protein (19 -22), and chromosome instability in non-malignant epithelial Madin-Darby canine kidney cells (18,23). Centrosomes, spindle pole bodies, are cellular organelles that exhibit an ability to organize microtubules and to nucleate (24).…”
Section: Mt1-mmpmentioning
confidence: 99%
“…In an efficient, but not yet completely understood manner, MT1-MMP acts as a growth factor in malignant cells and assumes tumor growth control (Hotary et al, 2003;Koshikawa et al, 2005). Our previous work has clearly shown that MT1-MMP confers tumorigenicity on non-malignant epithelial cells, thus providing us with substantive evidence of the enormous importance of this protease in cell functioning and, probably, in malignant transformation (Soulie et al, 2004).…”
Section: Discussionmentioning
confidence: 91%